Bioorganic studies of vision - Nakanishi, Koji (Henry Stewart Talks, 2008)
Visual pigments, Visual chromophores, Activation of Rh and beta-AR, Retinal / vitamin A cycle, Selective capture of retinoid binding proteins, Photocrosslinking of chromophore to Rh, Tracking the chromophore / opsin interaction, Rhodopsin photocycle, Photoaffinity labelling, Chromophore confirmation in Rh, Transient 'dark activity' of 13-des-Me-retinal, Retinoids that form pigments, Photoaffinity study of rhodopsin: G-protein (transducin) interaction, Age-related macular degeneration, Age pigments or RPE lipofuscin, A2E flurophore, ATP binding cassette protein, Bilberry extract vs. blue-light induced A2E epoxidation